Angular and CP-Violation Analyses of B-→D⁎+l-ν-l Decays at Hadron Collider Experiments - Daniele Marangotto (Advances in High Energy Physics)
The B-→D⁎+l-ν-l branching fractions ratio between muon and tau lepton decay modes R(D⁎) has shown intriguing discrepancies between the Standard Model prediction and measurements performed at BaBar, Belle, and LHCb experiments, a possible sign of beyond the Standard Model physics. Theoretical studies show how observables related to the B-→D⁎+l-ν-l differential decay distribution can be used to further constrain New Physics contributions, but their experimental measurements are lacking to date. This article proposes the measurement of B-→D⁎+l-ν-l angular and CP-violating observables at hadron collider experiments, by exploiting approximate reconstruction algorithms using information from detectable final-state particles only. The resolution on the phase space variables is studied using B-→D⁎+l-ν-l decays simulated in a forward detector geometry like LHCb. A method to correct the observable values for the reconstruction inaccuracies based on detector simulation is successfully tested on simulated data and the decrease in precision with respect to a perfect reconstruction is evaluated. The D⁎+ longitudinal polarization fraction and the AT(2)CP-violating observable can be measured losing a factor of 2 and 5 in precision, respectively. The extraction of angular distributions from the template fit selecting B-→D⁎+l-ν-l decays and associated systematic uncertainties are also discussed.